Cognition and the menopause transition. Issue 7 (July 2016) - Maki, Pauline M.; Henderson, Victor W.
Abstract : Complaints about forgetfulness, "brain fog, " and difficulty concentrating are common in women transitioning through menopause. Women with these cognitive complaints often express concern about whether these problems are normal, related to menopause, or represent a symptom of Alzheimer disease or another serious cognitive disorder. In this Practice Pearl, we provide a brief summary of the scientific literature on the frequency of cognitive complaints in midlife women, the validity of complaints in relation to performance on standardized cognitive tests, and the influence of menopause on cognitive performance. We then offer recommendations for healthcare providers and women to address cognitive concerns.